Reiter's syndrome postintravesical Bacillus Calmette–Guérin instillations - Ng, K.L.; Chua, C.B. (Elsevier, 2017)
Intravesical Bacillus Calmette–Guérin (BCG) has been a proven and effective immunotherapy treatment for superficial transitional cell carcinoma (TCC) of the bladder, especially for high-grade tumors and carcinoma in situ. Nevertheless, significant side effects are associated with BCG instillations, including fever, myalgia, malaise, dysuria, hematuria, and irritable lower urinary tract symptoms. We herein report the case of a patient who developed Reiter's syndrome following intravesical BCG instillations. A 39-year-old Chinese man presented with a 3-week history of dysuria, suprapubic pain, and pain at the tip of the penis postmicturition. Initial investigations revealed that he had microhematuria, and an ultrasound with computed tomography scan of the abdomen showed a bladder mass. Transurethral resection of the bladder tumor was performed and the patient received a single dose of intravesical mitomycin postoperatively. Results of histopathological examination revealed high-grade bladder TCC (G3pT1), and the patient was managed with intravesical BCG for 2 weeks following the surgery. Four weekly cycles of BCG were administered uneventfully; however, before the fifth instillation, the patient complained of urethral discharge, bilateral conjunctivitis, and low back pain. Reiter's syndrome was diagnosed as a rare but known complication of BCG instillation and the BCG immunotherapy was withheld. The patient was treated with nonsteroidal antiinflammatory drugs (for back pain) and eye ointment (for conjunctivitis) and his condition improved. This case report of Reiter's syndrome should be highlighted as a rare but significant complication of BCG immunotherapy and urologists should have a high index of suspicion to diagnose this rare complication.